Patriotisme économique et développement durable - Marie-Françoise Delaite; Jacques Poirot (Développement Durable et Territoires)
Economic patriotism is generally perceived as an invitation given to economic actors such as the State, consumers or companies, to facilitate national activities. The objective of this article is to show that economic patriotism is not only an instrument in the service of the industrial and commercial power of a State or a vector of its financial power, but that it is also perfectly compatible with the social and environmental dimensions of sustainable development. The concept of economic patriotism, in this respect, was examined in its traditional logics (Mercantilism, List and Keynes) and revisited in the optics of the theory of gift, introduced by Marcel Mauss and in the optics of Durkheim.